Peran Ulama Dayah Dalam Pembinaan Aqidah Umat Islam di Desa Sampoimah Kabupaten Aceh Timur - Syarifah Faradiba; Muhammad Muhammad; Endang Ekowati (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
In this research, the researcher examines the role of dayah Ulama in Fostering the Islamic Aqidah in Sampoimah Village, East Aceh Regency Sampoimah Village is one of the Villages located in the East Aceh Regency, Aceh Province. Aqidah is the main guideline for Muslims which refers to the belief in the nature of divinity. Dayah education facilities are one of the references in fostering aqidah within Muslims so that aqidah can be embedded more strongly in the hearts of every Muslims and what form a good character. Children will be encouraged to be more enthusiastic in learning.  As for the problem in this thesis, how is the role of ulama in fostering aqidah to Muslims and what factors motivate parents to send their children to Daya in Sampoimah Village, east Aceh Regency. Dayah has also become a real educational institution in the personal formation of children, this makes most parents enter their children into Dayah. The methodology used by the author in this study is a qualitative descriptive analysis method with field research. The data collection techniques were carried out by interviewing processed from the results of field observations and seeing village community activities. Data analysis was carried out using data collection, data filtering, data classification and conclusions. The results of this study were conducted in sampoimah Village, East Aceh District. Shows that this dayah does not have a special method to become a standard for learning in the dayah, the learning is carried out using only the same simple method as the method used at the time of the apostle, namely the question and answer method, sitting in halaqah and so on. But with this relatively simple learning, it is able to shape the character of the students whisch leads to positive things because of the responses from the students during the teaching and learning process.